1997
DOI: 10.1051/aas:1997204
|View full text |Cite
|
Sign up to set email alerts
|

New perceptions on the S Doradus phenomenon and the micro variations of five Luminous Blue Variables (LBVs)

Abstract: Abstract. We investigated the photometric histories of the LBVs HR Car in the Galaxy, R 127, R 110 and R 71 in the LMC, and R 40 in the SMC by collecting all available photometry. All these objects have been reasonably well observed over the last few decades and a number of "S Dor (SD) phases" (episodes of enhanced light) is well documented. Time-scales lie between 1.4 and 25 y. During the SD cycles two different types of micro-variations (amplitudes ∼ 0.m 2) are present: one near the minima (time-scale from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…Such behaviour is typical for LBVs in a normal S Dor (SD) phase, although the amplitude of the variation (in V , T eff and R ) observed in P Cygni is much smaller than those measured in other LBVs (van Genderen et al 1997a(van Genderen et al , 1997b. Thus, we conclude that over the timeperiod studied P Cygni has probably passed from a minimum (around 1988) to a maximum (around 1992) of a normal or SD-phase.…”
Section: Discussionsupporting
confidence: 52%
“…Such behaviour is typical for LBVs in a normal S Dor (SD) phase, although the amplitude of the variation (in V , T eff and R ) observed in P Cygni is much smaller than those measured in other LBVs (van Genderen et al 1997a(van Genderen et al , 1997b. Thus, we conclude that over the timeperiod studied P Cygni has probably passed from a minimum (around 1988) to a maximum (around 1992) of a normal or SD-phase.…”
Section: Discussionsupporting
confidence: 52%
“…Halfway between the two extrema the one is quickly replaced by the other, probably within a few months (e.g. van Genderen et al 1990van Genderen et al , 1997b. Both can only be seen simultaneously during this short transition stage.…”
Section: Resultsmentioning
confidence: 99%
“…Walborn & Fitzpatrick (2000), using absorptionline criteria, suggested that HR Car is a B3 Ia star, but the Mg ii λ 4481 / He i λ 4471 ratio indicates a B6-B7 spectral subtype. It should be kept in mind that HR Car, like other S Dor variables, is subject to a cyclic pattern of S Dor-phases with a time scale of years to decades (van Genderen et al 1997). Thus, brightness, spectrum, temperature, colour, etc., are cyclically variable.…”
Section: Introductionmentioning
confidence: 99%